ANALISIS KINERJA KEUANGAN DALAM PEROLEHAN DANA ZAKAT, INFAQ, DAN SHADAQAH PADA LAZISNU - Cholifatus Zahro; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the financial performance of a non-profit institution, namely LAZISNU and to determine the effectiveness of financial performance in 2018, 2019, and 2020. This study is a quantitative study and uses secondary data research taken from the 2018 Central LAZISNU financial report. and 2020. The instrument of this research is using organizational financial ratios. The data obtained were analyzed using measurements on 4 ratios, namely the liquidity ratio, solvency ratio, amil rights fund ratio, and activity ratio. A non-profit organization or non-profit institution is a form of organization where the main purpose of its establishment is not for profit alone but has a social mission (Nainggolan, 2012). The results of this study indicate that the analysis of financial performance at LAZISNU in 2018, 2019 and 2020 shows good results with measurements on each ratio that has a value according to good criteria. The limitation of this study is that the number of samples used is only one LAZ so that the data sources are limited and the researcher only analyzes financial performance without analyzing the effect of LAZ financial performance. For further research, it is recommended to multiply research data and discuss the effect of LAZ performance.Keywords: LAZISNU, Financial Performance, Financial Report